PENGARUH PROFITABILITAS, REPUTASI AUDITOR, UKURAN PERUSAHAAN, DAN KEPEMILIKAN INSTITUSIONAL TERHADAP AUDIT DELAY PADA PERUSAHAAN LQ-45 YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2015-2017 - Meida Puspita Dewi, 15.05.52.0238; Alfasadun, Alfasadun (Students' Journal of Accounting and Banking, 2019)
This study aimed to examines the influence of the profitability, reputation of auditors, company size, and ownership of institutional on the audit delay on LQ-45 companies listed on the Indonesia Stock Exchange. This research was conducted at Indonesia by using analysis unit LQ-45 company. The population of this research are LQ-45 company that listed in Indonesia Stock Exchange. The sampling method using purposive sampling with the study period of 2015 until 2017 and obtained as many as 34 companies. The data analysis technique used were descriptive statistics, classical assumption test, and multiple regression analysis. The results of this study shows that profitability and ownership of institutional does not affect on audit delay. The reputation of auditors significant positive influence on audit delay. The company size significant negative influence on audit delay.